Skill acquisition in sport : research, theory and practice - Hodges, Nicola J. ;Williams, A. Mark (London, United Kingdom : Routledge, 2012)
"Success in sport depends upon the athlete's ability to develop and perfect a specific set of perceptual, cognitive and motor skills. Now in a fully revised and updated new edition, Skill Acquisition in Sport examines how we learn such skills and, in particular, considers the crucial role of practice and instruction in the skill acquisition process. Containing thirteen completely new chapters, and engaging with the significant advances in neurophysiological techniques that have profoundly shaped our understanding of motor control and development, the book provides a comprehensive review of current research and theory on skill acquisition. Leading international experts explore key topics such as: attentional focus augmented Feedback observational practice and learning implicit motor learning mental imagery training physical guidance motivation and motor learning neurophysiology development of skill joint action. Throughout, the book addresses the implications of current research for instruction and practice in sport, making explicit connections between core science and sporting performance. No other book covers this fundamental topic in such breadth or depth, making this book important reading for any student, scholar or practitioner working in sport science, cognitive science, kinesiology, clinical and rehabilitation sciences, neurophysiology, psychology, ergonomics or robotics"
Part I : Presenting information -- Part II : Optimizing practice conditions -- Part III : Issues in motor learning -- Part IV : Skilled performance -- Part V : Research, theory and practices : challenges and solutions
Includes bibliographical references and index.
Keywords: SPORTS SCIENCE -- RESEARCH